Internationalisation of SMEs and simultaneous strategies of cooperation and competition: an exploratory analysis - Galdeano-Gómez, Emilio; Perez-Mesa, Juan C.; Aznar-Sánchez, José A. (Journal of Business Economics and Management, 2016)
The present work examines the relationships between SMEs’ marketing internationalisation and the combination of cooperation and competition strategies, i.e. co-opetition. Recent analyses have shown that the SMEs’ exports capabilities are highly dependent on co-opetition, while others suggest that the challenges of international supply chain constitute a major driver to this combination. This analysis contributes to the literature by providing empirical evidence on both of these issues. A multivariate regression analysis is developed, measuring variables of SMEs’ co-opetition and international activity, and taking as reference a set of 136 Andalusian food exporters. The results confirm the positive effect of strategies of cooperation with competitors (regarding logistics, promotion, quality and R&D) on international marketing activity. This positive effect is enhanced when large retailers are the main buyers, i.e. in hierarchical relationships. Furthermore, exporting activity is shown to promote co-opetition among suppliers. These findings highlight the importance of such strategies as regards both export capabilities of the food firms in this region and their expansion into new foreign markets. The empirical approach and certain implications drawn from the results can be extended to other analyses on SMEs in international contexts.